Coherent approach on radial oscillation indexes with AAOI for environmental ecosystem in the Southern/Antarctic Ocean - 永延, 幹男; 八木, 雅文; 轡田, 邦夫; Mikio, Naganobu; Masafumi, Yagi; Kunio, Kutsuwada (2015)
第6回極域科学シンポジウム 分野横断セッション：[IG] 全球環境変動を駆動する南大洋・南極氷床 11月17日（火） 国立極地研究所 2階 大会議室 conference object